BIMBINGAN KELOMPOK DENGAN TEKNIK MODELLING UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA KELAS VIII SMP NEGERI 1 PARONGPONG - Karmila, Dede; Rohaeti, Euis Eti; Rismawati Siddik, Riesa (IKIP Siliwangi, 2025)
Self-confidence means having confidence in one's own ability to act without depending on others, being optimistic, taking responsibility for one's actions, being polite in interacting with others, and realizing one's own strengths and weaknesses. Group guidance provides many benefits for students because they are indirectly actively involved in interactions with other group members. Modeling technique is a technique used to change a person's behavior, cognitive, and affective through the process of observation followed by the process of imitating the behavior of the model displayed. This research method is an experimental method with one group pretest-posttest. The population in this study were VIII grade students of SMP Negeri 1 Parongpong, totaling 82 students with 10 subjects. Sampling using purposive sampling. The results showed that the level of self-confidence increased after participating in group guidance services with modeling techniques as indicated by the results of the calculation of the Pretest average of 127.7000 and Postest of 165.8000 using Paired Samples Statistics and the significance level (2-tailed) of 0.000 <0.05 which means that modeling techniques in group guidance are effective in increasing self-confidence.